Literature Review: The Influence of Organizational Climate and Career Development on Organizational Commitment and Job Satisfaction - Sarifuddin, Muhammad; Christyanto, Frederikus Denny; Z, Zubaidah; Zalfanda H, Zenobia; Hidayati, Tetra (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
The strategy taken by the broadcasting media to improve the performance of its employees is to pay attention to job satisfaction and organizational commitment so that it can encourage the emergence of new creativity that can advance this institution. In order for this to be achieved, the broadcasting media must always pay attention to the work climate where employees carry out their duties, as well as monitor the career development of each employee. The purpose of this study is to find out and analyze the influence of organizational climate on organizational commitment with job satisfaction as an intervening variable in the broadcasting media on Jl. Putri Hijau. This type of research is literature review. The population in this study is all employees in the broadcasting media and the sampling technique is by stratified random sampling. In this study, the explanatory method was used and in data collection observation methods, questionnaires, interviews and literature studies were used. The results of the study show several previous studies on the variables Organizational Climate, Career Development, Organizational Commitment, and Job Satisfaction